Globalization and its methodological discontents: Contextualizing globalization through the study of HIV/AIDS - Labonté Ronald; Brown Garrett W (BMC, 2011)
Abstract There remains considerable discontent between globalization scholars about how to conceptualize its meaning and in regards to epistemological and methodological questions concerning how we can come to understand how these processes ultimately operate, intersect and transform our lives. This article argues that to better understand what globalization is and how it affects issues such as global health, we must take a differentiating approach, which focuses on how the multiple processes of globalization are encountered and informed by different social groups and with how these encounters are experienced within particular contexts. The article examines the heuristic properties of qualitative field research as a means to help better understand how the intersections of globalization are manifested within particular locations. To do so, the article focuses on three recent case studies conducted on globalization and HIV/AIDS and explores how these cases can help us to understand the contextual permutations involved within the processes of globalization.